Prevalence of malocclusion and associated habits in 4 to 6-year-old preschool children in Kuantan, Pahang - Abd Rahman, Mohamad Hafiz; Haris Fadzilah, Nur Aisyah; Nasir, Siti Hajjar; Che Musa, Muhd Firdaus (2020)
Introduction: This study was conducted to investigate the prevalence of malocclusion and their associated habit in the deciduous dentition of preschool children in the city of Kuantan, Malaysia. Material and methods: This study was conducted in IIUM Specialist clinic setting where the sample selected were children from 4 different preschools aged between 4-6 years old. Questionnaire and consent forms were distributed to their guardians and collected a week before the study. The children’s dentition was examined and all malocclusion present was recorded. The association between malocclusion and oral habits was analyzed using SPSS. Results: A total of 76 preschool children participated in this study and 55.3% of the children presented with dental malocclusion. The highest malocclusion recorded in sagittal direction was reduced overjet (28.9 %), whereas for malocclusion in transversal direction, midline deviation showed the highest percentage of 30.3%. Deep overbite showed the highest percentage of malocclusion in vertical direction which was 28.9%. Bottle feeding recorded the highest incident of oral habit with 23.7% followed by nail biting and object biting. A significant association between increase overjet and bottle feeding (p<0.05) as well as relationship between pacifier and anterior open bite (p<0.01) were established. Conclusion: The prevalence of malocclusion in primary dentition was high and significant association between oral habits and the development of malocclusion in deciduous dentition was demonstrated.